Composite of Hydroxyapatite-Fe3O4 for the Adsorption of Methylene Blue - Nur Hafizah Zainal Abidin; Nonni Soraya Sambudi; Norashikin Ahmad Kamal (ASEAN Journal of Chemical Engineering, 2020)
The utilization of hydroxyapatite as an adsorbent has been extensively tested to remove the dye and heavy metal. Yet the adsorbent loss to the environment may lead to secondary pollutant issues. Consequently, the hydroxyapatite was incorporated with Fe3O4 amount variation to solve the secondary pollutant problem by utilizing the magnetic properties of Fe3O4 to recollect the adsorbent. In this work, FESEM images showed a mixture of nano-sizes rods and spherical particles corresponded to the presence of hydroxyapatite and Fe3O4 as a composite. The study found that hydroxyapatite- Fe3O4 (100 wt %) could eliminate 12.434 mg methylene blue/g adsorbent after 4 hours. The hydroxyapatite also gained improvement in its surface area from 59.8m2/g to 75.2m2/g when Fe3O4 is added. In addition, the adsorption of methylene blue fits the Freundlich isotherms and pseudo-second-order kinetic model. Furthermore, the methylene blue removal using hydroxyapatite-Fe3O4 composite can be kept at 80% even after 4 times experiments, showing the recyclability of hydroxyapatite-Fe3O4.